Analisis Perbandingan Sistem Informasi Departemen F&B di Cafe ABC dan Hotel XYZ - Muhamad Azhari; Sri Anjani Ningsih; Elin Erlina Sasanti; Ni Made Rastini; Komang Ardhelia Ristianti (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2026)
Food and Beverage (F&B) services are an essential component in the hospitality industry that significantly influence customer satisfaction. Technological advancements have encouraged the implementation of information systems to improve operational efficiency and service quality. This study aims to analyze and compare the implementation of information systems in the F&B departments of Cafe ABC and Hotel XYZ. This research uses a descriptive qualitative method with data collection techniques through interviews and observations. The results show significant differences between the two objects, where Cafe ABC uses a semi-digital and simple system, while Hotel XYZ implements a fully integrated digital system. These differences are influenced by business scale, operational complexity, and organizational needs.